The Mediating Effect of Perceived Usefulness in the End-User Computing Satisfaction Model on Online Transportation User Satisfaction - Nardina Salsabila; Anang Muftiadi; Ria Arifianti (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The rapid growth of online transportation services in Indonesia has significantly reshaped urban mobility by offering greater convenience and efficiency. However, persistent issues such as system inaccuracies, usability problems, and information quality may affect user satisfaction. This study investigates the determinants of user satisfaction with an online transportation application by integrating the End-User Computing Satisfaction framework and the Technology Acceptance Model (TAM), with perceived usefulness serving as a mediating variable. A quantitative approach was applied using data collected from 390 active Maxim users in the Greater Jakarta area between January and March 2025. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that perceived usefulness has a strong and significant effect on user satisfaction. Accuracy, ease of use, and content quality significantly influence perceived usefulness, while timeliness and format do not. Furthermore, accuracy, ease of use, timeliness, and format directly affect user satisfaction, whereas content does not show a significant direct effect. These findings imply that online transportation providers should prioritize system accuracy, usability, timely information delivery, and interface design to enhance perceived usefulness and user satisfaction, thereby strengthening their competitive position.